Target DNA recognition using electrochemical impedance spectroscopy - Michaels, P.; Ciampi, Simone; Yean, C.; Gooding, J. (2010)
Electrochemical impedance spectroscopy was used to differentiate between different target DNA sequences without the use of a redox label or application of large bias voltages. This method relies on the formation of a mixed self-assembled monolayer (SAMs) composed of single-stranded DNA and a diluent, mercaptoethanol. Recognition of the DNA analytes was achieved through the significant increase in conductance for the double stranded DNA, as compared to single-stranded DNA. Non-complementary and single base-pair mismatches were also able to be differentiated. © 2010 IEEE.